Analisis Hasil Belajar Siswa Pada Pembelajaran IPA Fisika Kelas VII Sekolah Menengah Pertama - Durrotul Mufidah Inafah; Sigit Dwi Saputro (Universitas Hamzanwadi, 2024)
The aim of this research is to analyze student learning outcomes in science subjects using a lecture learning model for class VII middle school. The research method used was descriptive with a qualitative approach. The data collection techniques used are observation, interviews and documentation techniques. The data analysis technique used in the research is through data reduction, data presentation and drawing conclusions. Researchers used class VII A, totaling 32 students, as research objects. The result was 9 students who got a score (low), and 2 students who got a score (very low). The highest score for students in class VII science learning using the lecture method was 76 and the lowest score for student learning outcomes was 32. The average score for student learning outcomes in science learning using the lecture learning model was 57.78. Thus, the average value is in the interval 55-74 which is included in the medium category. The suggestion in this research is that there is a need for learning media that can help improve student learning outcomes in class VII science learning in junior high schools.